An exploratory study of respiratory muscle endurance training in high lesion level paraplegic handbike athletes - Fischer, G.; Tarperi, C.; George, K.; Ardigo, L. P. (Clinical Journal of Sport Medicine, 2014)
Objective: To investigate the impact of respiratory muscle endurance training (RMET) on lung function and exercise performance in athletes with high lesion level paraplegia.